Implementing Digital Governance for Improved Public Service Delivery in Lagos, Nigeria - Shintya, Bella (Asian Digital Governance Problems, 2025)
Purpose: This study explores the implementation of digital governance in Lagos, Nigeria, focusing on its impact on public service delivery, accountability, and citizen participation. As Nigeria’s economic hub and Africa’s largest megacity, Lagos provides a unique context for assessing the opportunities and challenges of digital governance in complex urban settings. Subjects and Methods: A mixed-methods approach was used. Quantitative data were collected from 420 residents through structured surveys assessing accessibility, satisfaction, efficiency, and trust in services such as online tax systems, e-health, and land registration. Qualitative insights were obtained from 15 interviews with policymakers, ICT experts, and service providers, along with two focus group discussions with community representatives. Results: Findings reveal that digital governance improves efficiency, reduces bureaucracy, and enhances transparency. Citizens expressed greater satisfaction with online services, though challenges persist, including low digital literacy, weak infrastructure, limited internet access, and institutional resistance. Marginalized communities remain underserved, reflecting a digital divide. Conclusions: Digital governance in Lagos holds transformative potential but requires improved infrastructure, digital education, and institutional commitment to achieve inclusive and equitable access.